(untitled) (Clinics, 2021)
OBJECTIVES: To evaluate the effects of sympathectomy on the myocardium in an experimental model. METHODS: The study evaluated three groups of male Wistar rats: control (CT; n=15), left unilateral sympathectomy (UNI; n=15), and bilateral sympathectomy (BIL; n=31). Sympathectomy was performed by injection of absolute alcohol into the space of the spinous process of the C7 vertebra. After 6 weeks, we assessed the chronotropic properties at rest and stress, cardiovascular autonomic modulation, myocardial and peripheral catecholamines, and beta-adrenergic receptors in the myocardium. The treadmill test consisted of an escalated protocol with a velocity increment until the maximal velocity tolerated by the animal was reached. RESULTS: The bilateral group had higher levels of peripheral catecholamines, and consequently, a higher heart rate (HR) and blood pressure levels. This suggests that the activation of a compensatory pathway in this group may have deleterious effects. The BIL group had basal tachycardia immediately before the exercise test and increased tachycardia at peak exercise (po0.01); the blood pressure had the same pattern (p=0.0365). The variables related to autonomic modulation were not significantly different between groups, with the exception of the high frequency (HF) variable, which showed significant differences in CT vs UNI. There was no significant difference in beta receptor expression between groups. There was a higher concentration of peripheral norepinephrine in the BIL group (p=0.0001), and no significant difference in myocardial norepinephrine (p=0.09). CONCLUSION: These findings suggest that an extra cardiac compensatory pathway increases the sympathetic tonus and maintains a higher HR and higher levels of peripheral catecholamines in the procedure groups. The increase in HF activity can be interpreted as an attempt to increase the parasympathetic tonus to balance the greater sympathetic activity.